2
$\begingroup$

The following problems are from Brown and Churchill's Complex Variables, 8ed.

From §71 concerning Residues and Poles, problem #1d:

Determine the residue at $z = 0$ of the function $$\frac{\cot(z)}{z^4} $$

I really don't know where to start with this. I had previously tried expanding the series using the composition of the series expansions of $\cos(z)$ and $\sin(z)$ but didn't really achieve any favorable outcomes. If anyone has an idea on how I might go about solving this please let me know. For the sake of completion, the book lists the solution as $-1/45$.

From the same section, problem #1e

Determine the residue at $z = 0$ of the function $$\frac{\sinh(z)}{z^4(1-z^2)} $$

Recognizing the following expressions:

$$\sinh(z) = \sum_{n=0}^{\infty} \frac{z^{(2n+1)}}{(2n +1)!}$$ $$\frac{1}{1-z^2} = \sum_{n=0}^{\infty} (z^2)^n $$

I have expanded the series thusly:

$$\begin{aligned} \frac{\sinh(z)}{z^4(1-z^2)} &= \frac{1}{z^4} \bigg(\sum_{n=0}^{\infty} \frac{z^{(2n+1)}}{(2n +1)!}\bigg) \bigg(\sum_{n=0}^{\infty} (z^2)^n\bigg) \\ &= \bigg(\sum_{n=0}^{\infty} \frac{z^{2n - 3}}{(2n +1)!}\bigg) \bigg(\sum_{n=0}^{\infty} z^{2n-4} \bigg) \\\end{aligned} $$

I don't really know where to go from here. Any help would be great.

Thanks.

$\endgroup$
3
  • $\begingroup$ @oldrinb I don't know. If $|z| < 1$ I would effectively be saying that $|\sum_{n=0}^\infty z^{2n}| = \sum_{n=0}^\infty \frac{1}{z^{2n}} $ ? $\endgroup$ – franklin Apr 21 '13 at 5:37
  • $\begingroup$ Do you know how to multiply polynomials? Multiplying these power series is similar. $\endgroup$ – obataku Apr 21 '13 at 5:56
  • $\begingroup$ see my response... $\endgroup$ – obataku Apr 21 '13 at 8:06
2
$\begingroup$

For the product of the two series, we aim for matching powers of $z$ and then take the Cauchy product of our coefficients:

$$\begin{align*}\frac1{z^4}\left(\sum_{n=0}^\infty\frac{z^{2n+1}}{(2n+1)!}\right)\left(\sum_{n=0}^\infty z^{2n}\right)&=\frac1{z^3}\left(\sum_{n=0}^\infty\frac{z^{2n}}{(2n+1)!}\right)\left(\sum_{n=0}^\infty z^{2n}\right)\\&=\frac1{z^3}\sum_{n=0}^\infty\left(\sum_{k=0}^n\frac1{(2k+1)!}\right)z^{2n}\\&=\sum_{n=0}^\infty\left(\sum_{k=0}^n\frac1{(2k+1)!}\right)z^{2n-3}\end{align*}$$For our residue, we're interested in the residue for $z=0$, we want the coefficient of $z^{-1}=z^{2(1)-3}$, which corresponds to $n=1$:$$\operatorname{Res}_{z=0}\frac{\sinh z}{z^4(1-z^2)}=\sum_{k=0}^1\frac1{(2k+1)!}=\frac1{1!}+\frac1{3!}=\frac76$$


For $\frac{\cot z}{z^4}$, first we rewrite $\cot z=\frac{\cos z}{\sin z}$:$$\frac{\cot z}{z^4}=\frac{\cos z}{z^4\sin z}$$Recall our familiar series expansions:$$\cos z=\sum_{n=0}^\infty\frac{(-1)^n z^{2n}}{(2n)!}=1-\frac{z^2}2+\frac{z^4}{4!}-\frac{z^6}{6!}+\dots\dots\\\sin z=\sum_{n=0}^\infty\frac{(-1)^nz^{2n+1}}{(2n+1)!}=z-\frac{z^3}{3!}+\frac{z^5}{5!}-\frac{z^7}{7!}+\dots$$Now, recognize that since we're interested in the residue for $z=0$, and our power series ends up divided by $\frac1{z^4}$, our coefficients are shifted backwards so we only need the coefficients for the first few terms of our power series. Let $\frac{\cos z}{\sin z}=a_{-1}z^{-1}+a_0z+a_1z^3+a_2z^5+a_3z^7+\dots$ so that:$$\left(z-\frac{z^3}{3!}+\frac{z^5}{5!}-\frac{z^7}{7!}+\dots\right)\left(a_{-1}z^{-1}+a_0z+a_1z^3+a_2z^5+a_3z^7+\dots\right)\\=1-\frac{z^2}2+\frac{z^4}{4!}-\frac{z^6}{6!}+\dots\\a_{-1}+a_0 z^2+a_1z^4+a_2z^6-\frac{a_{-1}}{3!}z^2-\frac{a_0}{3!}z^4-\frac{a_2}{3!}z^6+\frac{a_{-1}}{5!}z^4+\frac{a_0}{5!}z^6-\frac{a_{-1}}{7!}z^6+\dots\\=1-\frac{z^2}2+\frac{z^4}{4!}-\frac{z^6}{6!}+\dots\\a_{-1}+\left(a_0-\frac16a_{-1}\right)z^2+\left(a_1-\frac16a_0+\frac1{120}a_{-1}\right)z^4+\left(a_2-\frac16a_1+\frac1{120}a_0-\frac1{5040}a_{-1}\right)z^6+\dots\\=1-\frac{z^2}2+\frac{z^4}{4!}-\frac{z^6}{6!}+\dots$$ Equate coefficients for the first several terms:$$a_{-1}=1\\a_0-\frac16a_{-1}=-\frac12\implies a_0=-\frac13\\a_1-\frac16a_0+\frac1{120}a_{-1}=\frac1{24}\implies a_1=-\frac1{45}\\a_2-\frac16a_1+\frac1{120}a_0-\frac1{5040}a_{-1}=-\frac1{720}\implies a_2=-\frac2{945}$$Given this, we can write our power series for $\cot z$ as follows:$$\cot z=z^{-1}-\frac13z-\frac1{45}z^3-\frac2{945}z^5+\dots$$Now, divide through both sides by $z^4$ to yield our desired series:$$\frac{\cot z}{z^4}=z^{-5}-\frac13{z^{-3}}-\frac1{45}z^{-1}-\frac2{945}z+\dots$$Our residue is then merely the coefficient of our $z^{-1}$ term:$$\operatorname{Res}_{z=0}\frac{\cot z}{z^4}=-\frac1{45}$$

$\endgroup$
0
3
$\begingroup$

A related problem. Lets consider your first problem

$$ \frac{\cot(z)}{z^4}=\frac{\cos(z)}{z^4\sin(z)}. $$

First, determine the order of the pole of the function at the point $z=0$, which, in this case, is of order $5$. Once the order of the pole has been determined, we can use the formula

$$r = \frac{1}{4!} \lim_{z\to 0} \frac{d^4}{dz^4}\left( z^5\frac{\cos(z)}{z^4\sin(z)} \right)=-\frac{1}{45}. $$

Note that, the general formula for computing the residue of $f(z)$ at a point $z=z_0$ with a pole order $n$ is

$$r = \frac{1}{(n-1)!} \lim_{z\to z_0} \frac{d^{n-1}}{dz^{n-1}}\left( (z-z_0)^n f(z) \right) $$

Note: If $z=z_0$ is a pole of order one of $f(z)$, then the residue is

$$ r = \lim_{z\to z_0}(z-z_0)f(z). $$

$\endgroup$
2
  • 1
    $\begingroup$ I think he intends for it to be derived explicitly using a Laurent series, but nice work! $\endgroup$ – obataku Apr 21 '13 at 7:36
  • $\begingroup$ @oldrinb: Thanks for the comment. $\endgroup$ – Mhenni Benghorbal Apr 21 '13 at 12:50
2
$\begingroup$

$$\cos z=1-\frac{z^2}{2}+\frac{z^4}{24}-\ldots\;,\;\;\;\sin z=z-\frac{z^3}{6}+\frac{z^5}{120}-\ldots\implies$$

$$\cot z=\frac{\left(1-\frac{z^2}{2}+\frac{z^4}{24}-\ldots\right)}{z\left(1-\left(\frac{z^2}{6}-\frac{z^4}{120}\right)+\mathcal O(z^6)\right)}=$$

$$=\frac{1}{z}\left(1-\frac{z^2}{2}+\frac{z^4}{24}-\ldots\right)\left(1+\left(\frac{z^2}{6}-\frac{z^4}{120}\right)+\left(\frac{z^2}{6}-\frac{z^4}{120}\right)^2+\ldots\right)=$$

$$=\frac{1}{z}\left(1-\frac{z^2}{2}+\frac{z^4}{24}-\ldots\right)\left(1+\frac{z^2}{6}-\frac{z^4}{120}+\frac{z^4}{36}-\frac{z^6}{360}+\frac{z^8}{120^2}+\ldots\right)$$

$$=\frac{1}{z}\left(1-\frac{z^2}{3}-\frac{z^4}{45}+\ldots\right)=\frac{1}{z}-\frac{z}{3}-\frac{z^3}{45}+\mathcal O(z^5)$$

Multipying the above by $\,\displaystyle{\frac{1}{z^4}}\;$ renders the residue $\,\displaystyle{-\frac{1}{45}}\,$ .

Notice we only use the powers necessary to calculate the coefficient of $\,z^{-1}\,$ . All the rest is unimportant to us.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.